Project Based Learning with Flipbook Media: Discourse Analysis Approach in Learning Biographical Texts - Daulay, Febriani; Arif, Syamsul; Adisaputera, Abdurahman (Journal of Pragmatics and Discourse Research, 2024)
Biographical texts are material in the Indonesian language subject for class However, in this learning process, problems are still found in learning components such as curriculum, objectives, materials, strategies, methods and learning evaluation so that learning objectives are not achieved. The aim of this research is to find out the process, form, validity and effectiveness of developing biographical text teaching materials in improving students' ability to analyze biographical text discourse. The method used is research and development. The results of the development of teaching materials were obtained by a development process using the define, design and develop model. The form of developing teaching materials from textbooks into interactive flipbook teaching materials with a project based learning model. The material expert validation results were 90% and the media expert validation results were 85% in the very valid category. The learning results showed that 0 students or 0% got the predicate D (grades 60-69). There were 5 students who received a C predicate (grades 70-79) or 25% and 10 students who received a B predicate (80-89) or 50% and 5 students who received an A predicate (90-100) or 25%. From the validation results and student learning outcomes, the teaching materials were declared valid and effective.